2016
DOI: 10.1164/rccm.201509-1795oc
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed Chronic Obstructive Pulmonary Disease Contributes to the Burden of Health Care Use. Data from the CanCOLD Study

Abstract: Most subjects with COPD in Canada remain undiagnosed. These subjects are less symptomatic and impaired, which may partly explain lack of diagnosis. Although patients with undiagnosed COPD experience fewer exacerbations than those with diagnosed COPD, they use a similar amount of health services for exacerbation events; thus, the overall health system burden of exacerbations in those with undiagnosed COPD is considerable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 33 publications
5
89
1
Order By: Relevance
“…those requiring health care utilization including emergency department (ED) visits and/or hospital admissions) among undiagnosed COPD patients is similar to that among diagnosed individuals. 12 These findings further support the need to diagnose COPD using objective measures when symptoms are present, in order to prevent this morbidity by providing proper therapy. Spirometry is a safe, practical and reproducible breathing test that can be used in primary care to objectively determine lung function.…”
Section: Spirometry Measurements In Targeted Populations For Case Finmentioning
confidence: 65%
See 2 more Smart Citations
“…those requiring health care utilization including emergency department (ED) visits and/or hospital admissions) among undiagnosed COPD patients is similar to that among diagnosed individuals. 12 These findings further support the need to diagnose COPD using objective measures when symptoms are present, in order to prevent this morbidity by providing proper therapy. Spirometry is a safe, practical and reproducible breathing test that can be used in primary care to objectively determine lung function.…”
Section: Spirometry Measurements In Targeted Populations For Case Finmentioning
confidence: 65%
“…19 In the CanCOLD study, individuals with diagnosed COPD reported 0.63 exacerbations per person-year. 12 Overall, exacerbations of any severity were reported by 40%, and moderate to severe exacerbations by 32% of individuals with diagnosed COPD. An important and achievable goal of therapy in the management of stable COPD is to decrease the frequency and reduce the severity of AECOPD.…”
Section: Summary Of Evidencementioning
confidence: 91%
See 1 more Smart Citation
“…However, it remains unclear how beneficial diagnosing these "missed" individuals would be (41)(42)(43). An uncomfortable tension exists between ensuring those with clinically relevant COPD are correctly identified and appropriately treated versus overmedicalizing individuals with mildly abnormal spirometric results.…”
Section: Case Finding and Accurate Diagnosismentioning
confidence: 99%
“…A concept that was firstly reported for congestive heart failure (CHF) (80% undiagnosed CHF in COPD) by Rutten et al 35 more than 10 years ago, and recently re-addressed in review articles 36,37 .…”
mentioning
confidence: 99%